Evaluating the Effectiveness of Differentiated Branding Strategies for Sustainable Products Utilizing Recycled Plastics in Hungary - Sarközi, David; Szabo, Zoltan (Journal of Entrepreneurship, Business and Economics, 2025)
The paper provides valuable insights into the most effective branding strategies applicable to sustainable products, highlighting their key influences on brands, corporates, products and consumers. Furthermore, the research identifies the preferences and awareness levels of Hungarian consumers, revealing key factors and elements for making sustainable products more appealing in Hungary. The study is based on an extensive literature review that covers all relevant findings in this field, complemented by non-representative quantitative empirical research conducted through a standardized online survey in the focus country. The findings indicate that, among other factors, sourcing transparency, eco-labels, certifications, and influencer marketing can contribute positively to making this product category more appealing, while improving brand image and perception. The primary research reveals that sustainability is a significant factor influencing Hungarian consumers' product choices. These consumers are familiar with such items; specific features and the way they are branded are having a significant effect on shaping buyers´ purchasing decisions. The results of the study are expected to crucially support corporate efforts in effectively selecting and implementing branding strategies for sustainable products utilizing recycled plastics targeting the Hungarian market. Research Paper Keywords: Branding Strategies, Sustainability, Sustainable Branding, Recycled Plastics, Social Responsibility, Green Branding Reference to this paper should be made as follows: Sarközi, D., & Szabo, Z. (2024). Evaluating the Effectiveness of Differentiated Branding Strategies for Sustainable Products Utilizing Recycled Plastics in Hungary. Journal of Entrepreneurship, Business and Economics , 12 (2), 109–135.